Impact of a stakeholder selected implementation strategy package – fast tracking, provider re-training, and co-location – on PrEP implementation for pregnant women in antenatal care clinics in western Kenya - Joseph Sila; Anjuli Dawn Wagner; Felix Abuna; Julia C Dettinger; Ben Odhiambo; Nancy Ngumbau; George Oketch; Enock Sifuna; Laurén Gómez; Sarah Hicks; Bryan J. Weiner; Grace John-Stewart; et al. (Implementation Science Communications)
Abstract Background Pre-exposure prophylaxis (PrEP) is recommended for HIV prevention in pregnant and postpartum women at substantial ongoing risk for HIV. In resource-limited settings, there exist gaps in the integration of PrEP into antenatal care. Methods We conducted a difference-in-differences analytic approach (3 months pre- and 3 months post) between January 2022 and July 2022 in 8 facilities (4 intervention and 4 comparison) in western Kenya. During the 6-month period, we tested a combination of 2 stakeholder selected implementation strategies – retraining health providers and fast tracking PrEP clients– to improve PrEP delivery. All study facilities dispensed PrEP in the Maternal and Child health clinics (MCH). We evaluated absolute changes in: PrEP penetration, PrEP fidelity, client PrEP knowledge, client satisfaction, and client waiting and service times as outcomes specified a priori while PrEP offer and HIV testing were outcomes specified post hoc. We measured acceptability and appropriateness by providers of the implementation strategies using AIM and IAM respectively. Results We observed statistically significant improvements in PrEP penetration and PrEP offer (p < 0.05) and non-significant improvements in fidelity. PrEP penetration increased 6 percent points (p = 0.002), PrEP offer increased nearly 6 percentage points (p = 0.002), and PrEP fidelity increased 4 percentage points (p = 0.202) in intervention vs comparison facilities. Client PrEP knowledge increased 0.45 out of 7 total points (p < 0.001) and PrEP screening increased 13 percentage points (p = 0.001). We observed no significant changes in service time (0.13-min increase; p = 0.249), waiting time (0.03-min decrease; p = 0.796), or client satisfaction (0.04/24 total point decrease; p = 0.849) in intervention vs comparison facilities. HIV testing did not significantly change (7 percentage point decrease, p = 0.305). The implementation strategy bundle was deemed appropriate and acceptable by the providers (appropriateness: 18.5/20; acceptability: 18.5/20). Overall, the implementation strategy bundle was associated with larger increases in implementation outcomes among women receiving a visit other than their first ANC visit, as well as among sites without stockouts of HIV test kits. Conclusions A stakeholder-selected implementation strategy bundle that included retraining healthcare workers, fast tracking PrEP clients to reduce waiting time, and PrEP dispensing in MCH improved several implementation outcomes without significantly affecting waiting time or reducing service time.